2009
DOI: 10.1080/01674820902789233
|View full text |Cite
|
Sign up to set email alerts
|

Previous birth experience and birth anxiety: predictors of caesarean section on demand?

Abstract: As negative birth experience predicts the wish for a CS, specific supportive care during first pregnancy could play a pivotal role in making this decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 17 publications
0
47
0
2
Order By: Relevance
“…Nevertheless, it is important to acknowledge that many women have suffered negative experiences during childbirth, and there are often negative consequences of retaining the negative memories for a prolonged period. Some studies have revealed that negative childbirth experiences may lead to serious consequences such as post-traumatic stress disorder [3], maternal depression [14], opting for caesarean section at subsequent childbirth [15], and subsequent low fertility [16]. Previous research has shown that caregiver support during labor is related to childbirth experience [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to acknowledge that many women have suffered negative experiences during childbirth, and there are often negative consequences of retaining the negative memories for a prolonged period. Some studies have revealed that negative childbirth experiences may lead to serious consequences such as post-traumatic stress disorder [3], maternal depression [14], opting for caesarean section at subsequent childbirth [15], and subsequent low fertility [16]. Previous research has shown that caregiver support during labor is related to childbirth experience [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…This can have adverse effects on the relationship with their partner and the bond with their baby (Elmir et al, 2010). Negative experiences are also associated with avoidance of a subsequent pregnancy (Gottvall and Waldenström, 2002;Porter et al, 2006) and a wish for an elective caesarean section in future births (Hildingsson et al, 2002;Tschudin et al, 2009). …”
Section: Introductionmentioning
confidence: 96%
“…Cultural factors, the structure of antenatal care and delivery services, as well as how they are funded, are likely to influence preferences for CS [14]. However, it may be argued that the perception of the upcoming birth is deeply embedded in a woman's personality and prior experiences, including traumas [15][16][17][18]. Based on this assumption, reported preference for CS would not be related to external factors and thus may not vary across countries.…”
Section: Introductionmentioning
confidence: 99%